2020
DOI: 10.3390/cryst10040304
|View full text |Cite
|
Sign up to set email alerts
|

Anion–Cation Recognition Pattern, Thermal Stability and DFT-Calculations in the Crystal Structure of H2dap[Cd(HEDTA)(H2O)] Salt (H2dap = H2(N3,N7)-2,6-Diaminopurinium Cation)

Abstract: The proton transfer between equimolar amounts of [Cd(H 2 EDTA)(H 2 O)] and 2,6-diaminopurine (Hdap) yielded crystals of the out-of-sphere metal complex H 2 (N3,N7)dap [Cd(HEDTA)(H 2 O)]·H 2 O (1) that was studied by single-crystal X-ray diffraction, thermogravimetry, FT-IR spectroscopy, density functional theory (DFT) and quantum theory of "atoms-in-molecules" (QTAIM) methods. The crystal was mainly dominated by H-bonds, favored by the observed tautomer of the 2,6-diaminopurinium(1+) cation. Each chelate anion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
0
1
Order By: Relevance
“…В системе Cd 2+ − H2NCH2COOH -H2O наблюдаются следующие равновесия комплексообразования: [18,19]. По дан-ным [20] [32]. Во всех известных этилендиаминтетраацетатах катион кадмия(+2) проявляет к. ч.…”
Section: комплексообразование кадмия (+2) с аминоацетат- аминодиацета...unclassified
“…В системе Cd 2+ − H2NCH2COOH -H2O наблюдаются следующие равновесия комплексообразования: [18,19]. По дан-ным [20] [32]. Во всех известных этилендиаминтетраацетатах катион кадмия(+2) проявляет к. ч.…”
Section: комплексообразование кадмия (+2) с аминоацетат- аминодиацета...unclassified
“…A bond path and bond critical point (CP) interconnecting two atoms can be used as an unambiguous indication of interaction [26]. Moreover, this type of analysis has been recently used in similar systems [27][28][29][30][31]. The distribution of bond CPs and bond paths of the two motifs analyzed above are shown in Figure 14.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…In reference [24], Belmont-Sanchez et al reported the synthesis and X-ray characterization of several out-of-sphere cadmium complexes with 2,6-diaminopurine. The crystal packing of these compounds is mostly dominated by H-bonds, which were analyzed by using DFT calculations.…”
mentioning
confidence: 99%